2014
DOI: 10.1007/s00276-014-1266-x
|View full text |Cite
|
Sign up to set email alerts
|

The potential effect of anatomic relationship between the femur and the tibia on medial meniscus tears

Abstract: The impact of femorotibial incongruence on the medial meniscus tear is important for the understanding of the lesions.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
5
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(6 citation statements)
references
References 13 publications
1
5
0
Order By: Relevance
“…Final findings about discrepancy of the femur on the tibia are close but not strictly comparable to the work of Wahl et al [17] and Bozkurt et al [18] that suggested an association between meniscus tears and femorotibial compartment congruency in patients with acute ACL ruptures, defined by a less concave medial tibial plateau articulating with a more convex medial femoral condyle.…”
Section: Discussionsupporting
confidence: 72%
See 1 more Smart Citation
“…Final findings about discrepancy of the femur on the tibia are close but not strictly comparable to the work of Wahl et al [17] and Bozkurt et al [18] that suggested an association between meniscus tears and femorotibial compartment congruency in patients with acute ACL ruptures, defined by a less concave medial tibial plateau articulating with a more convex medial femoral condyle.…”
Section: Discussionsupporting
confidence: 72%
“…There is, however, an abundance of research investigating anatomic risk factors for isolated ACL rupture (excessive tibial slope [1012], intercondylar notch width [13, 14], lateral morphology of the knee [1517]). Limited prior work evaluating risk factors associated with meniscus pathology has suggests decreased femorotibial congruency, excessive tibial rotation, and a discrepancy between femoral condyle and the tibial plateau lengths may play a role [1820].…”
Section: Introductionmentioning
confidence: 99%
“…Several parameters are related to the width of the femoral notch (11,12), such as the notch width (NW), bicondylar notch width (BCW), the notch width index (NWI), condyle width of the femur, tibial spine height, and intercondylar angle. However, limited prior studies evaluated the anatomical risk factors for the injury of meniscus (21)(22)(23)(24).…”
Section: Introductionmentioning
confidence: 99%
“…Furthermore, these injuries have an incidence of 60–70 per 100,000 patients affecting young, active individuals and can occur in isolation or in tandem with other injuries such as ACL tears. 24 Studies have shown the medial meniscus is affected more than the lateral due to differences in meniscal anatomy and articular geometry. 5,6…”
Section: Introductionmentioning
confidence: 99%
“…Furthermore, these injuries have an incidence of 60-70 per 100,000 patients affecting young, active individuals and can occur in isolation or in tandem with other injuries such as ACL tears. [2][3][4] Studies have shown the medial meniscus is affected more than the lateral due to differences in meniscal anatomy and articular geometry. 5,6 An ACL deficiency causes four times the typical amount of anterior tibial translation (ATT) and consequently places additional demands on the medial meniscus to act as the knee's primary stabilizer in the anterior-posterior, internalexternal and varus-valgus directions.…”
Section: Introductionmentioning
confidence: 99%